Absorption, metabolism, and excretion of [14C]YY-20394, a highly selective PI3K-Delta inhibitor in humans. (4th March 2022) - Yu, Jinghua; Zhang, Hua; Zhang, Yifan; Zhan, Yan; Ma, Sheng; Hu, Tao; Zhang, Ning; Lou, Yangtong; Bao, Hanying; Xu, Zusheng; Zhong, Dafang; Miao, Liyan; et al.
Abstract: YY-20394, a highly selective PI3Kδ inhibitor, is under NDA submission for treating follicular lymphoma in China. The absorption, metabolism, and excretion of YY-20394 were evaluated in healthy Chinese male subjects following a single oral dose of 80 mg [ 14 C]YY-20394 (100 µCi). Within 264 h post-dose, 92.1% of the administered dose was recovered, with 58.1% from urine and 34.0% from faeces. YY-20394 was rapidly absorbed in humans, and the peak plasma concentrations occurred at 1.0 h. The absorbed drug fraction was at least 58.1% according to urine recovery. In addition to the parent drug, nine metabolites were identified in plasma, urine, and faeces. Unchanged YY-20394 was the predominant drug-related component in plasma (accounting for 68.4% of the total radioactivity), urine (accounting for 90.0% of the urinary radioactivity) and faeces (accounting for 41.7% of the faecal radioactivity). In humans, the major metabolic sites were the morphine ring and side chains of piperidine rings. The major metabolic pathways involved N -dealkylation, O -dealkylation, glucuronidation and acetylation. Overall, renal elimination played a significant role in the disposition of YY-20394, and the morphine ring and the side chain of the piperidine ring was the predominant metabolic sites.